Descrição e acesso do acervo de plantas da Fortaleza de São José da Ponta Grossa da ilha de Santa Catarina - Lutz, Cristiano Cavalheiro (2018)
The military fortifications of the Island of Santa Catarina, dating from the eighteenth century, are highlighted as some of the most important architectural elements in the state due to its monumental architecture and the landscape formed by it. Next to the Fortresses of Santa Cruz and Santo Antônio, the Fortress of São José da Ponta Grossa formed a triangular system of defense of the North Barra of Island. In view of the above, the present work seeks to elaborate an inventory of the architectural and engineering plans of the São José da Ponta Grossa Fortress of Santa Catarina Island, based on the Brazilian Standard of Archival Description (NOBRADE), aiming at access and diffusion of the collection, considered as archival documentary heritage of the Federal University of Santa Catarina (UFSC). Of the more than 500 plants and projects present in the UFSC collection, 121 belong to the São José da Ponta Grossa Fortress, the focus of this work. The work contextualizes the aspects of the history of the monument object of the study; maps the context of the documentary production and makes a survey of the current conservation conditions of the collection.